Beyond decolonial African philosophy
1 online resource (xvi, 303 pages).
Keywords: "Beyond Decolonial African Philosophy dives into decoloniality discourse, challenging some of its shortcomings and offering alternative perspectives on the nature of Africanity and Afrotopia (Africa's better future) from leading African philosophers. Beginning with an overview of philosophy in contemporary Africa, the first half of the book goes on to critically interrogate and rethink decoloniality's deconstructivist approach. The second half of the book considers a range of alternative new conceptualizations of Afrotopia and Africanity that transcend decolonial theory, drawing on constructivist and creative approaches. The book considers key questions such as: Is Africanity immutable (essentialism), or mutable (nominalism)? Should we emphasise idealist, identitarian concerns, or pragmatic, developmentarian concerns? Should we prioritise African agency, or structures and circumstances? Should Africa embrace hybrid interculturality and creative self-manifestive identity or essentialist purity? Drawing on rich insights from African philosophers across the continent, this book challenges students and researchers to think beyond the concept of decolonization to alternative forms of African identities and African futures"--